Histopathological Characteristics of Gastrointestinal Stromal Tumors in a Cohort of Vietnamese Patients - Pham Nguyen Cuong; Nguyen Thanh Xuan; Tran Xuan Tien; Pham Nhu Huy; Pham Nguyen Tuong (SAGE Publishing, 2020)
Introduction: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal system. Histopathological examination takes an important part in confirming the subtypes of GISTs, to choose appropriate therapeutics for patients. This study aims to explore the histopathological characteristics and evaluate the relationship between malignant risk classification (according to Armed Forces Institute of Pathology criteria) and the histopathological features of GISTs in a cohort of Vietnamese patients. Methods: We reviewed 89 patients with primary GIST who underwent surgery between 2014 and 2019 at Hue Central Hospital, Vietnam. We investigated histopathological characteristics and immunohistochemical findings of all patients. Results: The average age was 55.9 ± 11.9 years. A tumor size of 2-5 cm accounted for 64.1%. The most common position was at the stomach which accounted for 48.5%. Among the subtypes of GIST, spindle cells were seen in 85.9% of patients; epithelial form 10.9%; multi-morphology (3.2%). 97.4% of the samples were positive for CD117, 61.5% of cases were positive for CD34; and no case was positive for Desmin. The rate of high-risk GIST was dominant (46.9%) as compared to the intermediate-risk (28.1%), low-risk (0.3%-2%), and very low-risk groups (4.7%). Conclusions: This study demonstrates the histopathological characteristics of GIST and emphasizes the significant rate of high-risk GIST.